On the effect of draft tube rod protrusion on runner blade stress fatigue of single-regulated axial turbines - Shahab Shiraghaee; Joel Sundström; Erik Olsson; Mehrdad Raisee; Michel J. Cervantes (Discover Applied Sciences)
Abstract Under off-design and transient operations of hydraulic turbines, these machines are subjected to harmful pressure fluctuations originating from the presence of vortical flow. These oscillations increase stress-induced fatigue damage on the turbine runner, shortening turbine life and reducing its reliability. This study investigates how cylindrical rods in the draft tube affect the runner blade strains and their consequent fatigue damage during transient and off-design steady-state operations. Different part-load conditions of an axial model turbine and two transients between speed-no-load and best efficiency point were experimentally studied using time-resolved pressure and runner blade strain measurements. The proposed adjustable flow control technique effectively reduced the runner damage, particularly at lower loads where reductions as high as 70% were obtained. In addition, draft tube pressure data were used for fatigue estimation, and a correlation with blade stress damage was observed at lower loads where high-amplitude load cycles occurred. The results showed that different protrusion lengths should be used function of the prevailing operating condition to obtain optimal damage reductions with lower efficiency penalties. Therefore, the proposed technique can provide an adjustable solution that mitigates off-design pressure oscillations and their consequent damage while limiting efficiency losses.